(untitled) (Al-Academy, 2021)
The national anthem is one of the most eloquent communicative discourses that the language establishes due to its deep impact on the audience and forms a broad mass base that interacts with the chanting of the national anthem. Moreover, communication is the cornerstone in building social and educational relations. From this point of view, the communicative approach studies language in the communicative context and its six important functions identified by linguist Roman Jacobson. The official UAE national anthem is considered as a model for expressing the enthusiasm of the Emirati Arab public, who is proud of their Arabism, loyalty and love of the homeland, because of the expressions that this anthem carries, urging the public to national unity and peace, preserving the inherited traditions, the progress and development of the country and drawing the public’s attention and interaction in performance to enhance national identity. From this perspective, this research seeks to study the communicative functions manifested in the Emirati national anthem and the impact of this anthem (the sender) on the audience (the addressee) according to the descriptive-analytical approach. Accordingly, this study provides flashes on some topics such as expressive function, emotional function, Metalinguistic function, cognitive function and poetic function.